Investigation of Microprocessor-based Current Protection of Distribution Networks Lines - F. A. Romaniuk; E. V. Buloichyk (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
As a result of computing experiment the basic indices of the technical perfection of microprocessor current protection of distribution networks lines were obtained. Test data are presented in the form of signal dependences in various protection circuits. Estimation of an operating capability and efficiency of the investigated protection under two- and three-phase short circuits at the beginning and end of the protected line and also at the end of an adjacent transmission line with a transient resistance were carried out in the paper. The paper proves an efficiency and high sensitivity of the proposed method which ensures a selective and proper operation of the protection in all modes of the controlled transmission line.